2014
DOI: 10.1155/2014/970385
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Herbal Complexes Containing Licorice on Potassium Levels: A Retrospective Study

Abstract: To observe the influence of these complexes on potassium levels in a clinical setting, we investigated the influence of herbal complexes containing licorice on potassium levels. We retrospectively examined the medical records of patients treated with herbal complexes containing licorice from January 1, 2010, to December 31, 2010. We recorded the changes in the levels of potassium, creatinine, and blood urea nitrogen and examined the differences between before and after herbal complexes intake using a paired t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…It is also consistent with reported associations between increased urinary potassium and increased airway hyper responsiveness [35] and also lower lung function in girls [36] and lower levels of serum potassium were associated with a greater risk of asthma [37]. However, there are studies that report no association of serum potassium and asthma.…”
Section: E) Herbal Medications and Potassium Levels F) Lung Diseases And Potassium Levelssupporting
confidence: 89%
See 1 more Smart Citation
“…It is also consistent with reported associations between increased urinary potassium and increased airway hyper responsiveness [35] and also lower lung function in girls [36] and lower levels of serum potassium were associated with a greater risk of asthma [37]. However, there are studies that report no association of serum potassium and asthma.…”
Section: E) Herbal Medications and Potassium Levels F) Lung Diseases And Potassium Levelssupporting
confidence: 89%
“…It is tempting to speculate that the anti-covid activity of such plant extracts could also be through the route of balancing the levels of potassium ions in the human body which needs to be experimentally proven in COVID patients. There are some conflicting reports on inability of Glycyrrhiza glabra (licorice) extract to influence the potassium levels in humans [29] and the potassium levels were normal in 98.3% patients with a dose of 8.7 g per day for 18 days. Also, some herbal drugs which are used a laxatives like Cassia senna L may lead to hypokalemia, since senna can cause excessive water and potassium loss.…”
Section: I) Potassium and Mental Healthmentioning
confidence: 99%
“…However, in five patients, the hypokalemia did not appear to be related to the licorice. This investigation suggested that herbal complexes containing licorice did not significantly influence the potassium levels in routine clinical herbal therapies [160]. In another study, 4T1 mammary carcinoma cells were injected into the mammary fat pads of syngeneic BALB/c mice.…”
mentioning
confidence: 90%
“…In a study involving 360 subjects, no clinically significant change in renal function (potassium, blood urea nitrogen, and creatinine levels) were found in 98.3% of the subjects after ~19 days of ~8 g licorice per day taken as dietary supplements that contained other ingredients. The remaining 1.7% of subjects developed hyperkalemia [62]. In a safety and toxicity study with 39 healthy female and male volunteers aged 19-40 years old, glycyrrhizic acid was administered at 1, 2, and 4 mg/kg body weight daily for 8 weeks.…”
Section: Licorice Toxicitymentioning
confidence: 99%